Electrical Impedance Tomography for Robot-Aided Internal Radiation Therapy - Tan, Hao; Rossa, Carlos (Frontiers in Bioengineering and Biotechnology, 2021)
High dose rate brachytherapy (HDR) is an internal based radiation treatment for prostate cancer. The treatment can deliver radiation to the site of dominant tumour growth within the prostate. Imaging methods to delineate the dominant tumour are imperative to ensure the maximum success of HDR. This paper investigates the feasibility of using electrical impedance tomography (EIT) as the main imaging modality during robot-aided internal radiation therapy. A procedure utilizing brachytherapy needles in order to perform EIT for the purpose of robot-aided prostate cancer imaging is proposed. It is known that cancerous tissue exhibits different conductivity than healthy tissue. Using this information, it is hypothesized that a conductivity map of the tissue can be used to locate and delineate cancerous nodules via EIT. Multiple experiments were conducted using 8 brachytherapy needle electrodes. Observations indicate that the imaging procedure is able to observe differences in tissue conductivity in a setting that approximates transperineal HDR and confirm that brachytherapy needles can be used as electrodes for this purpose. The needles can access the tissue at a specific depth that traditional EIT surface electrodes cannot. The results indicate the feasibility of using brachytherapy needles for EIT for the purpose internal radiation therapy.